Osteoarticular Expression of Musashi-1 in an Experimental Model of Arthritis. (3rd May 2015) - O'Valle, Francisco; Peregrina, Magdalena; Crespo-Lora, Vicente; Galindo-Moreno, Pablo; Roman, Maria; Padial-Molina, Miguel; Mesa, Francisco; Aneiros-Fernandez, Jose; Aguilar, David; Gonzalez-Rey, Elena; Delgado, Mario; Hernandez-Cortes, Pedro
Abstract : Background . Collagen-induced arthritis (CIA), a murine experimental disease model induced by immunization with type II collagen (CII), is used to evaluate novel therapeutic strategies for rheumatoid arthritis. Adult stem cell marker Musashi-1 (Msi1) plays an important role in regulating the maintenance and differentiation of stem/precursor cells. The objectives of this investigation were to perform a morphological study of the experimental CIA model, evaluate the effect of TNF α -blocker (etanercept) treatment, and determine the immunohistochemical expression of Msi1 protein. Methods . CIA was induced in 50 male DBA1/J mice for analyses of tissue and serum cytokine; clinical and morphological lesions in limbs; and immunohistochemical expression of Msi1. Results . Clinically, TNF α -blocker treatment attenuated CIA on day 32 after immunization (P < 0.001 ). Msi1 protein expression was significantly higher in joints damaged by CIA than in those with no lesions (P < 0.0001 ) and was related to the severity of the lesions (Spearman's rho = 0.775, P = 0.0001 ). Conclusions . Treatment with etanercept attenuates osteoarticular lesions in the murine CIA model. Osteoarticular expression of Msi1 protein is increased in joints with CIA-induced lesion and absent in nonlesioned joints, suggesting that this protein is expressed when the lesion is produced in order to favor tissue repair.